Visual object interface signifier of museum application for large display - Mohammad Shuhaili, F. (Springer Verlag, 2017)
The use of signifiers, commonly known as affordances, in designing an interface should be given a careful attention since signifiers have been poorly applied especially for large multitouch display. The huge interactional space creates a challenge to the design process. This paper investigates visual object interface signifiers of museum application for a large display in order to support navigation. A user study was conducted with ten of participants interacting with the museum interface, running on a Microsoft SUR40 tabletop. The study findings revealed information on (i) suitable signifiers for a large display and, (ii) features of visible object interface signifiers. Among the suitable signifiers for navigation in the environment are arrow, text or numbers, menu button, and floor map. These findings could be useful for the development of museum interfaces on a large display. © Springer International Publishing AG 2017.